Reducing Reducing Patient's Pain with Post Coronary Artery Bypass Graft (CABG) by Performing Foot Massage: A Systematic Review - Pamungkas, Indra Gilang; Herawati, Tuti; Prima Agustia Nova (Babali Nursing Research, 2023)
Introduction: Pain is one of the conditions experienced by patients after Coronary Artery Bypass Graft (CABG). It affects physical function, professional life, relationships and family life, social life, sleep patterns, and mood. Foot massage which is one of the complementary therapies can be done by pressing the reflective area of the foot to release endorphins so that pain will be reduced. This study aimed to review the effect of foot massage on the pain level of patients with post-CABG patients. Methods: Systematic review was used using 5 databases namely: ProQuest, ScienceDirect, Google Scholar, ClinicalKey Nursing, and Sage Journal. Articles were selected with the criteria of having been published within the 2018-2022, using English or Indonesian, and patients in the first phase. The Articles were evaluated using JBI and ended up with 5 articles. Results: The results showed that the total number of respondents in this study was 331 people with the majority is male (64.35%). Five articles showed a significant effect between foot massage and pain in patients after CABG with a p-value (p < 0.05). Conclusion: Foot massage can improve hemodynamic status and reduce pain in CABG patients. Feelings of relaxation and decreased stress are associated effectively to affect hemodynamic status and pain.